2000
DOI: 10.1093/ptr/10.4.390
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Among Attachment Representation, Emotion-Abstraction Patterns, and Narrative Style: A Computer-Based Text Analysis of the Adult Attachment Interview

Abstract: The main aim of this research was to test the discriminant capacity of computer-based, linguistic text measures which are economically compilable (Emotion-Abstraction Patterns, Mergenthaler, 1996; Computerized Referential Activity, Mergenthaler & Bucci, 1999) in differentiating between complex attachment representations in the Adult Attachment Interview (Main & Goldwyn, 1994). The study of N = 40 healthy controls produced the consistent result that, of the two insecure attachment categories, the group 'dismiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 16 publications
1
20
1
5
Order By: Relevance
“…This finding is consistent with our previous research that suggests heightened communication of emotion for mothers with Preoccupied attachments compared to Autonomous and Dismissing attachments, but only under conditions of infant distress (Milligan et al, 2003). Similarly, Buchheim (2000) found that adult attachment-related differences in emotional communication of the AAI only reached significance when emotional valence of words was examined as a moderator, with adults with Preoccupied attachments showing the highest use of negative emotion words.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding is consistent with our previous research that suggests heightened communication of emotion for mothers with Preoccupied attachments compared to Autonomous and Dismissing attachments, but only under conditions of infant distress (Milligan et al, 2003). Similarly, Buchheim (2000) found that adult attachment-related differences in emotional communication of the AAI only reached significance when emotional valence of words was examined as a moderator, with adults with Preoccupied attachments showing the highest use of negative emotion words.…”
Section: Discussionsupporting
confidence: 92%
“…This pattern of findings is consistent with previous research examining the relation between adult attachment and emotional communication. Buchheim (2000) found that individuals with Preoccupied attachments were significantly more likely to verbalize emotions during the AAI interview than those individuals with Dismissing attachments, with individuals with Autonomous attachments falling between these two groups in terms of their emotion verbalization. Similarly, Whipple, Bernier, and Mageau (2011) found that Preoccupied states of mind were associated with a more intrusive style compared to Dismissing states of mind.…”
Section: Discussionmentioning
confidence: 88%
“…Associations between attachment status and the capacity to represent affects have also been reported for adults; there is evidence from several studies that insecure attachment is related to alexithymia (Blumberg, 1997;Montebarocci, Codispoti, Baldaro, & Rossi, 2004;Scheidt et al, 1999;Troisi, D'Argenio, Peracchio, & Petti, 2001;Waller, E., Scheidt, & Waller, N., in prep.). The theoretical assumption of a specific link between dismissing attachment and alexithymia was supported only in those studies relying on the scoring system of Main (Main & Goldwyn, 1985 for attachment classification (Blumberg, 1997;Buchheim & Mergenthaler, 2000;Scheidt et al, 1999;Waller et al, in prep.). There is also evidence from several other studies that dismissing attachment is clearly linked to defensive forms of affect regulation (Dozier & Kobak, 1992;Fraley, Garner, & Shaver, 2000;Mikulinker & Orbach, 1995;Zeijlmans van Emmichoven, van IJzendoorn, De Ruiter, & Brosschot, 2003).…”
Section: Aetiology Of Dysregulated Affects In Somatoform Disorders: Amentioning
confidence: 99%
“…In fact it was the sexual offenders, not the neurotic patients, who displayed the greatest amount of Connecting. Buchheim and Mergenthaler (2000) report an observation, where subjects with an avoidance attachment style tended to have less Connecting whereas preoccupied subjects had more Connecting that those who were securely attached. Our present findings then make sense if the sexual offender subjects are considered as preoccupied.…”
Section: Discussionmentioning
confidence: 99%